Desarrollo histórico de la Enseñanza Médica Superior en Cuba de 1959 a 1989 - Flavia Linares Tovar; Claudia Katerine López Palmero; Yainara Abreus Ponvert (Medisur)
The triumph of the Revolution led to a series of changes in the health system. Hence, the revolutionary period is considered the upper stage of medical teaching in Cuba. This paper analyzes the development of Higher Medical Education in Cuba from 1959 to 1989. The situation in the country at the beginning of the Revolution was taken as a starting point. Aspects related to the achievements in health professional training, teaching methods, curricula and the network of medical schools throughout the country are discussed. The period analyzed was the scene of major changes and steps forward to achieve teaching, practical and research integration based on the community problems and needs.